Characterization and pathogenicity of fungi associated with anthracnose of chilli (capsicum frutescens L.) (Bangladesh Journal of Botany, 2024)
A total of nine fungal species were isolated from the anthracnose infected  chilli fruits. The fungi associated with infected chilli fruits were Alternaria alternata  (Fr.) Keissler, A. tenuissima (Kunze ex Pers.), Aspergillus flavus Link, A. niger van Tieghhm, Colletotrichum dematium (Pers.) ex Fr., C. gloeosporioides (Penz.) Sacc., Curvularia clavata Wakker, Fusarium semitectum Berk. & Rav. and Rhizopus stolonifer (Ehrenb.) Vull. Among the isolated fungi, Colletotrichum dematium (49.03), C. gloeosporoides (18.06) and Fusarium semitectum (20.12) showed the higher per cent frequency. Out of nine fungal species, Colletotrichum dematium, C. gloeosporioides and Fusarium semitectum were found to be pathogenic to chilli fruits.Bangladesh J. Bot. 53(1): 49-55, 2024 (March)